PEMWE를 위한 Cs치환에 따른 공유가교 SPEEK/Cs(x)-TPA/Ceria막의 합성 및 특성 연구 - 황성하(Sung Ha Hwang); 박대영(Dae Young Park); 오승희(Seung Hee Oh); 윤대진(Dae Jin Yoon); 오연선(Yun Sun Oh); 서현(Hyeon Seo); 강안수(An Soo Kang); 문상봉(Sang Bong Moon); 정장훈(Jang Hoon Chung) (한국수소 및 신에너지학회 논문집, 2014)
CL-SPEEK/Cs-TPA/$CeO_2$ composite membrane was prepared for polymer electrolyte membrane water electrolysis (PEMWE). In order to improve the electrochemical, mechanical, durabilities and electrocatalytic characteristics, engineering plastic of polyether ether ketone (PEEK) as polymer matrix was sulfonated and the organic-inorganic blend composite membranes was prepared by loading cesium-substituted tungstophosphoric acid (Cs-TPA) by titration method with cross-linking agent contents of 0.01mL. Ceria ($CeO_2$) was used to scavenge free radicals which attack the membrane in the PEMWE circumstance and to increase the duration of the membrane. CL-SPEEK/$Cs_{(1)}$-TPA/CeriaIn conclusion, 1% membrane showed the optimum results such as 0.119 S/cm at $80^{°}C$ of proton conductivity and 62MPa of tensile strength.